Highly conductive titania supported iridium oxide nanoparticles with low overall iridium density as OER catalyst for large-scale PEM electrolysis. (September 2021) - Böhm, Daniel; Beetz, Michael; Gebauer, Christian; Bernt, Maximilian; Schröter, Jonas; Kornherr, Matthias; Zoller, Florian; Bein, Thomas; Fattakhova-Rohlfing, Dina
Abstract: To enable future large-scale generation of hydrogen via proton exchange membrane (PEM) electrolysis, utilization of scarce iridium-based catalysts required for the oxygen evolution reaction (OER) has to be significantly lowered. To address this question, the facile synthesis of a highly active TiO2 supported iridium oxide based OER catalyst with reduced noble metal content and an Ir-density of the catalyst powder as low as 0.05–0.08 gIr cm -3 is described in this work. A high surface area corrosion-resistant titania catalyst support homogeneously coated with a 1-2 nm thin layer of amorphous IrOOHx is oxidized in molten NaNO3 between 350-375°C. This procedure allows for a controllable phase transformation and crystallization to form a layer of interconnected IrO2 nanoparticles of ≈2 nm on the surface of the TiO2 support. The increase in crystallinity is thereby accompanied by a significant increase in conductivity of up to 11 S cm -1 for a 30 wt% Ir loaded catalyst. Oxidized samples further display a significantly increased stability with less detectable Ir dissolution under OER conditions. With a mass-based activity of 59 A g -1 at an overpotential of 300 mV, the electrocatalytic activity is maintained at the level of the highly active amorphous IrOOHx phase used as precursor and outperforms it at higher current densities through the increased conductivity. MEA measurements with catalyst loadings of 0.2-0.3 mg cm -2 further confirm the high catalytic activity and initial stability at industrially relevant current densities. The introduced synthesis approach therefore shows a path for the fabrication of novel highly active and atom-efficient oxide supported catalysts with complex nanostructures and thin homogenous nanoparticle coatings that allows a future large-scale application of PEM electrolysis technology without restrictions by the natural abundance of iridium. Graphical abstract: Image, graphical abstract